2020
DOI: 10.1039/d0cy01056a
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of [B,H]ZSM-5 by a solid-phase method: AlF siting and catalytic performance in the MTP reaction

Abstract: Boron-isomorphous substituted HZSM-5, [B,H]ZSM-5 zeolite was directly synthesized by solid-phase method and the properties were characterized by XRD, FESEM, N2 adsorption/desorption, FT-IR, ICP-AES, NH3-TPD, py-FTIR, TG, GC-MS, solid MAS NMR...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…42 For example, more acid sites appeared in the supercage and/or intersection cavity of zeolites can relatively enhance the aromatics cycle and produce more ethene and aromatic species, whereas the acid sites siting in the 10-membered ring (10-MR) channel are more encouraging for the propagation of the alkene cycle, thus preferentially generating propylene and butene. 9,43…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 For example, more acid sites appeared in the supercage and/or intersection cavity of zeolites can relatively enhance the aromatics cycle and produce more ethene and aromatic species, whereas the acid sites siting in the 10-membered ring (10-MR) channel are more encouraging for the propagation of the alkene cycle, thus preferentially generating propylene and butene. 9,43…”
Section: Resultsmentioning
confidence: 99%
“…42 For example, more acid sites appeared in the supercage and/or intersection cavity of zeolites can relatively enhance the aromatics cycle and produce more ethene and aromatic species, whereas the acid sites siting in the 10membered ring (10-MR) channel are more encouraging for the propagation of the alkene cycle, thus preferentially generating propylene and butene. 9,43 Therefore, in order to investigate the distribution of Al F in relation to different morphologies of ZSM-5 in the MTP 10c. In order to analyze the NMR spectra in greater detail, peak fitting was conducted for each sample, as shown in Fig.…”
Section: Location and Distribution Of Al Atoms Within The Zsm-5 Zeoli...mentioning
confidence: 99%
See 1 more Smart Citation
“…34 Acidity is a key parameter for determining the catalytic performance of zeolite catalysts. 35,36 The NH 3 -TPD curves of four catalysts displayed the existence of two types of acid sites: weak and strong acid sides, corresponding to the desorbed ammonia below and above 300 °C, respectively (see Figure S13 in the Supporting Information). The acid amounts of samples were calculated based on the peak areas of the NH 3 -TPD curves and compiled in Table S2 in the Supporting Information.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The acidity of Al-IDM-1 samples was first characterized. The 27 Al MAS NMR spectra of Al-IDM-1 samples (Figure S6c) with different Si/Al ratios displayed that nearly all the Al atoms were tetra-coordinated in framework. The NH 3 -TPD curves showed that two peaks decreased obviously in intensity with the Si/Al ratio increasing from 50 to 600 (Figure S2C), and the calculated total acid amount decreased from 262.3 to 17.5 μmol • g À 1 (Table S2).…”
Section: Resultsmentioning
confidence: 99%